NET BUYING (SELLING) INVESTOR ASING DAN PERUBAHAN KURS TERHADAP PERGERAKAN INDEKS PASAR - Setyawan, Ignatius Roni (Journal of Management and Business, 2007)
The article tested net buying selling in Jakarta Stock Exchange. JSX index stated an amazing leap during 2006 however the performance was affect by foreign investor rather than domestic investors. The research indicates that net buying selling forces by foreign investors and the fund transfer during transaction will affect the foreign exchange rate (USD to IDR). The study argues the increasing rate of net buying selling also increase the volatility of exchange rate. Using TARCH model, the research found significant result that supported the argument. The research also test the robustness of data using stationary test. Therefore, the result statistically hold and TARCH model plus AR (1) also hold during the analysis.